A comprehensive screening shows that ergothioneine is the most abundant antioxidant in the wild macrofungus Phylloporia ribis Ryvarden. (3rd April 2018) - Zhao, Hengqiang; Zhang, Minmin; Liu, Qian; Wang, Xiaoli; Zhao, Ruixuan; Geng, Yanling; Wong, Tityee; Li, Shengbo; Wang, Xiao
ABSTRACT: The polar and non-polar extracts from the authenticated wild mushroom Phylloporia ribis were separated by hydrophilic interaction liquid chromatography (HILIC) and by reverse phase (RP)-HPLC, respectively. A split valve separated the eluents into two fractions for free-radical scavenging analysis and for structural identification. Forty-six compounds showed scavenging activity of the stable-free radical 2, 2-diphenyl-1-picrylhydrazyl (DPPH). The structures of 8 antioxidants (inosine, caffeic acid, ergothioneine, p-hydroxybenzoic acid, adenosine, 3, 4-dihydroxybenzaldehyde, apigenin, and naringenin) are characterized by Mass Spectrometer. Among them, ergothioneine was the most abundant (>65%) and most active antioxidant in P. ribis .